Sistema regional de inovação em turismo um estudo sobre o estado de Alagoas - Barros, André Taboza (2018)
In a national scenario of economic and regional recession to reduce tourist activities, tourism in Alagoas has been positive for some years. Assuming that innovation is a factor of competitiveness for destinations and tourist regions, this research uses the methodology survey allied to the methodology for innovation of the OECD to address the gap of scientific work encompassing the theme and the geographical delimitation of Alagoas, suggesting the existence of a Regional System of Innovation in Tourism in Alagoas, identifying the interactions between firms and the institutions that compose it, analyzing their evidence of cooperation, learning, knowledge generation and technological diffusion. After the mapping and analysis of the system, it was submitted theories of Regional System of Innovation and Regional System of Innovation in Tourism, resulting in a system of low innovation potential for the first theory and a moderate system in innovation, for the second theory.